1980
DOI: 10.1038/285017a0
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of the pigments of life: formation of the macrocycle

Abstract: The organic nuclei of chlorophylls, haems, cytochromes and vitamin B12 are biosynthesised from a single tetrapyrrolic intermediate which has an unexpected, rearranged structure. The mechanism of biosynthesis of this key intermediate has now been characterised in detail. Some of the information thereby obtained is also of use in the investigation of human diseases such as the porphyrias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
151
1
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(157 citation statements)
references
References 24 publications
3
151
1
2
Order By: Relevance
“…Now, Protoporphyrin IX is an important precursor to biologically essential prosthetic groups such as cytochrome C in mammals and chlorophylls in herbs. As a result, a number of organisms are able to synthesize Protoporphyrin IX from basic precursors such as glycine and succinyl CoA, or glutamate [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Now, Protoporphyrin IX is an important precursor to biologically essential prosthetic groups such as cytochrome C in mammals and chlorophylls in herbs. As a result, a number of organisms are able to synthesize Protoporphyrin IX from basic precursors such as glycine and succinyl CoA, or glutamate [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that A. nidulans dissimilated nitrate to generate ammonium via NO 2 Ϫ under hypoxic conditions (36). We also reported that hypoxic A. nidulans cells accumulate NO 2 Ϫ , which damages purine residues of DNA (33). A recent report has suggested that A. nidulans NAD(P)H-NO 2 Ϫ reductase (NiR, the product of the niiA gene) plays a potential role in NO detoxification by sequestering NO-generating NO 2 Ϫ (32).…”
mentioning
confidence: 99%
“…Microorganisms generate NO as an intermediate of denitrification (10). Bacterial nitrification and denitrification processes involve nitrite (NO 2 Ϫ ) as an intermediate, and improper aeration often results in the accumulation of NO 2 Ϫ , which is concentration-dependently dismutated to NO, especially in an acidic environment (43). Thus, NO is ubiquitous in the microbial milieu, and exposure to NO 2 Ϫ and NO should induce microbial mechanisms to survive RNS toxicity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 Both haemin (the oxidized ferric form of heme [haem], also called hematin [haematin]) and chlorophyll are members of a family of vivid compounds, the modified tetrapyrroles or porphyrins, which Sir Alan Battersby dubbed the "pigments of life" 5,6 and which Nature uses in numerous roles in the biosphere among the broad gamut of its varied life forms. 7 Porphura, the origin of the word porphyrin, and all its related variations, comes from ó o (porphuros) the Greek for purple.…”
mentioning
confidence: 99%